Epidemiology, isolation and genetic diversity study of Saprolegnia in rainbow trout (Oncorhynchus mykiss) in the hatcheries of Kashmir - Mushtaq, Syed Aalia; Ahmed, Irfan; Balkhi, M. H.; Shah, Feroz; Mushtaq, Syed Aalia (Journal of the Inland Fisheries Society of India, 2021)
The present study was conducted to isolate and characterise the genetic variations in Saprolegnia species and to study epidemiology of the fungal infection in rainbow trout hatcheries of Kashmir. A total of 145 infected fish samples were examined during October to March. The fungus infected trout showed signs of lethargy, irritation, loss of appetite, haemorrhages at the base of fins and deep wounds at the sites of severe infection associated with cottony wool like tufts on both dorsal and ventral side of body. Wet mount from infected lesions showed masses of mature and immature sporangia filled with spores of Saprolegnia. The colonies on fungal agar appeared with tufly of long hairs, whitish in colour that finally turned blackish after some days. The hyphae appeared profusely branched, aseptate and multinucleate. A total of 29 DNA samples were amplified by RAPD-PCR which revealed negligible genetic variations among the isolates indicating that a group of closely related strains of Saprolegnia having high degree of homology was present in the hatcheries of Kashmir. Key words Fungus, Fish, Cotton-wool disease, RAPD, Winter Introduction